Social determinants of health impacting adherence to diabetic retinopathy examinations - Cindy X Cai; Melissa L McCarthy; Yixuan Li; Scott L Zeger (BMJ Open Diabetes Research & Care)
Introduction This study evaluates the association of multidimensional social determinants of health (SDoH) with non-adherence to diabetic retinopathy examinations.Research design and methods This was a post-hoc subgroup analysis of adults with diabetes in a prospective cohort study of enrollees in the Washington, DC Medicaid program. At study enrollment, participants were given a comprehensive SDoH survey based on the WHO SDoH model. Adherence to recommended dilated diabetic retinopathy examinations, as determined by qualifying Current Procedural Terminology codes in the insurance claims, was defined as having at least one eye examination in the 2-year period following study enrollment.Results Of the 8943 participants enrolled in the prospective study, 1492 (64% female, 91% non-Hispanic Black) were included in this post-hoc subgroup analysis. 47.7% (n=712) were adherent to the recommended biennial diabetic eye examinations. Not having a regular provider (eg, a primary care physician) and having poor housing conditions (eg, overcrowded, inadequate heating) were associated with decreased odds of adherence to diabetic eye examinations (0.45 (95% CI 0.31 to 0.64) and 0.70 (95% CI 0.53 to 0.94), respectively) in the multivariate logistic regression analysis controlling for age, sex, race/ethnicity, overall health status using the Chronic Disability Payment System, diabetes severity using the Diabetes Complications Severity Index, history of eye disease, and history of diabetic eye disease treatment.Conclusions A multidimensional evaluation of SDoH revealed barriers that impact adherence to diabetic retinopathy examinations. Having poor housing conditions and not having a regular provider were associated with poor adherence. A brief SDoH assessment could be incorporated into routine clinical care to identify social risks and connect patients with the necessary resources to improve adherence to diabetic retinopathy examinations.